Rol de Klotho y FGF23 en la regulación del fosfato y calcio plasmático - Toro C., Luis (Revista Hospital Clínico Universidad de Chile, 2010)
Recently, two proteins have been discovered, named Klotho and FGF23, which are involved in several physiologic phenomena. One of the most relevant is the reduction of phosphatemia and the increase of phosphaturia. This effect is mainly caused by the activation of the membrane receptor FGFR1 by a joined action of Klotho and FGF23 (called Klotho/FGF23 pathway). It has been proved that Klotho/FGF23 suppresses production and secretion of parathyroid hormone (PTH) in parathyroid gland, reduces active vitamin D levels by inhibition of 1α-hydroxylase synthesis and increased expression of 24-hydroxylase in the kidney. It is also described that FGF23 expression is promoted by active vitamin D and plasmatic phosphate. Because of that, it has been proposed the existence of a bone-kidney-parathyroid endocrine axis, which regulates serum phosphate levels. Although it has not been studied yet, it is likely that Klotho and FGF23 also have a role in regulation of serum calcium levels, due to the effects of Klotho/FGF23 over key calcium regulators. The discovery of Klotho/FGF23 axis has expanded our knowledge concerning the endocrine mechanisms of the calcium-phosphate metabolism, and it might also help in the development of new clinical approaches and treatments of calcium and phosphate disorders.